1991
DOI: 10.1111/j.1570-7458.1991.tb01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfhydryl‐reagent alteration of soybean resistance to the cabbage looper, Trichoplusia ni

Abstract: The hypothesis that the sulfhydryl reagent, N‐ethylmaleimide, would function as an elicitor of alterable resistance in soybean (Glycine max) plants to Trichoplusia ni herbivory was tested experimentally under greenhouse conditions. This elicitory chemical, which allows receptor thiols to add across its carbon‐carbon double bond, altered the resistance in one or more leaves of plants at one or more intervals after treatment; and thus yielded results supporting the hypothesis. Leaf dipping and soil application w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…An elicitor apparently just The elicitory effects of vitamin C were influenced by dosage, time after treatment and space in the plant. Comparable influences on the systemic dimensions of elicitation were noted previously in G. max (Neupane & Norris 1990, 1991a. Regarding the effects of dosage, the only significant alterations by 10 -» to 10 -3 M L-ascorbic acid were increases in anti-herbivory.…”
Section: Vitamin C Elicitationsupporting
confidence: 62%
See 2 more Smart Citations
“…An elicitor apparently just The elicitory effects of vitamin C were influenced by dosage, time after treatment and space in the plant. Comparable influences on the systemic dimensions of elicitation were noted previously in G. max (Neupane & Norris 1990, 1991a. Regarding the effects of dosage, the only significant alterations by 10 -» to 10 -3 M L-ascorbic acid were increases in anti-herbivory.…”
Section: Vitamin C Elicitationsupporting
confidence: 62%
“…6 cork borer. Two leaf discs, one from the appropriate leaf on a treated (elicited) plant and the other from the same leaf on a control plant, were each secured with its abaxial surface up in an opposed position, 3 cm apart, in the center of a 9 cm diam plastic petridish arena (Neupane & Norris 1990, 1991a. Each arena contained a 3 mm-deep bed of paraffin covered by a Whatman No.…”
Section: Bioassaying Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of induced glyceollin and coumestrol in a given soybean hypocotyl depended on seedling age, the chemical The efficiency of chemicals as elicitors differs significantly even among the tested sulfhydryl-binding reagents, IAA, PMBS, and AgNO3, which are confirmed inducers of phytoalexins, especially glyceollin, in soybean (15,16,25). The order of efficiency of these chemicals as elicitors of glyceollin and coumestrol in Davis hypocotyls was AgNO3 > PMBS >> IAA, but in PI 227687 hypocotyls the order was AgNO3 2 PMBS >> IAA.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding chemical elicitors, some classical sulfhydryl-binding reagents mimic insects in the induction of phytoalexin (e.g. glyceollin) accumulation in fully developed soybean plants (15,16). Stossel (24,25) also showed that sulfhydrylbinding reagents could induce glyceollin accumulation in soybean hypocotyls.…”
mentioning
confidence: 99%